A design-based pedagogical framework for developing computational thinking skills. Issue 4 (2nd October 2022) - Gupta, Samrat; Tiwari, Amit Anand
ABSTRACT: Despite of advances in computational methods for a variety of real-world problems, there is a lack of holistic educational approaches for developing Computational Thinking (CT) skills of students. The CT skills develop students' ability to design and implement solutions using information systems development process. This paper describes how a soft computing-based multi-faceted modelling approach for solving the interdisciplinary problem of community detection in social networks can be used for developing CT skills among students. We use Design Science Research (DSR) process to design the proposed educational framework. The proposed educational framework has been implemented using R programming environment. Evaluation and feedback of students who undertook a couple of sessions establish the viability of the proposed educational framework.